KEUNGGULAN SDM DAN BERDAYA SAING TERHADAP KINERJA PT. BANK TABUNGAN NEGARA TBK CABANG DENPASAR PADA MASA PANDEMI COVID-19 - Putu Ari Mulyani; Ni Made Yusmini; Adonia Putriyanti Sara Dima (Jurnal Ilmiah Satyagraha, 2023)
Bank is an institution that acts as an intermediary that connects partieswho have excess funds with those who lack funds in the form of savings andchannel them again to the public in the form of credit or other forms, which aimsto improve the standard of living of the community considering its very importantfunction for the wheels of the economy and life. Public. the banking industry musthave superiority SDM good and have high competitiveness and have good performance. Therefore, a study was carried out with the title Excellence SDMand competitive on performance PT. Bank Tabungan Negara Tbk CabangDenpasar during the covid-19 pandemic. This study aims to examine theExceelence of SDM and Competitiveness of Performance PT. Bank TabunganNegara Tbk Cabang Denpasar. The sample in this study were employess PT. BankTabungan Negara Tbk Cabang Denpasar. The research method used in thisresearch is quantitative research using descriptive methods. The process focollecting research data using a questionnaire distribution technique to 56respondents and processed using SPSS. The data analysis technique in this studyis multiple linear regression using the SPSS (Statistical Package For SocialScience) version 23 application. The results obtained by the author are that theadvantages of SDM positive and significant effect on performasce,competitineness has a positive and significant effect on performance, SDMexcellence and competitiveness together have a positive and positive effect onperformance PT. Bank Tabungan Negara Tbk Cabang Denpasar.